Enhancing PGMI Students’ Conceptual Understanding through a Contextual Teaching and Learning-Based Science E-Module - Fitriyah Ika Astutik; Fitri Nur Rohmah (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to develop a science e-module based on Contextual Teaching and Learning (CTL) to improve the conceptual understanding of students of the PGMI Study Program of IAI Al-Khairat Pamekasan. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were PGMI IAI Al-Khairat Pamekasan students taking the Science Study course in the 4th semester of 2025. Research data were collected through observation, interviews, questionnaires, and tests. The instruments used included expert validation sheets, student response questionnaires, and pretest and posttest questions. Data were analyzed using the Aiken's V index to test validity, percentage analysis to measure practicality, and N-gain to determine product effectiveness. The results showed that the developed e-module obtained an average validity of 0.87 with a very valid category. The results of the practicality test showed a percentage of 86.75% with a very practical category. The results of the effectiveness test showed an increase in students' conceptual understanding, marked by an increase in the average pretest score from 61.42 to 84.28 in the posttest, with an N-gain value of 0.59 in the moderate category. Based on these results, the CTL-based Science e-module was declared valid, practical, and effective for use in Science Studies learning. This e-module is expected to be an alternative digital teaching material that supports independent, interactive, and contextual learning for PGMI students.